Mutation in the mouse histone gene Hist2h3c1 leads to degeneration of the lens vesicle and severe microphthalmia. (November 2019) - Vetrivel, Sharmilee; Tiso, Natascia; Kügler, Andrea; Irmler, Martin; Horsch, Marion; Beckers, Johannes; Hladik, Daniela; Giesert, Florian; Gailus-Durner, Valerie; Fuchs, Helmut; Sabrautzki, Sibylle; Hrabě de Angelis, Martin; et al.
Abstract: During an ENU ( N -ethyl- N -nitrosourea) mutagenesis screen, we observed a dominant small-eye mutant mouse with viable homozygotes. A corresponding mutant line was established and referred to as Aey69 (abnormality of the eye #69). Comprehensive phenotyping of the homozygous Aey69 mutants in the German Mouse Clinic revealed only a subset of statistically significant alterations between wild types and homozygous mutants. The mutation causes microphthalmia without a lens but with retinal hyperproliferation. Linkage was demonstrated to mouse chromosome 3 between the markers D3Mit188 and D3Mit11 . Sequencing revealed a 358 A-> C mutation (Ile120Leu) in the Hist2h3c1 gene and a 71 T-> C (Val24Ala) mutation in the Gja8 gene. Detailed analysis of eye development in the homozygous mutant mice documented a perturbed lens development starting from the lens vesicle stage including decreasing expression of crystallins as well as of lens-specific transcription factors like PITX3 and FOXE3. In contrast, we observed an early expression of retinal progenitor cells characterized by several markers including BRN3 (retinal ganglion cells) and OTX2 (cone photoreceptors). The changes in the retina at the early embryonic stages of E11.5-E15.5 happen in parallel with apoptotic processes in the lens at the respective stages. The excessive retinal hyperproliferation is characterized by an increased level of Ki67. The hyperproliferation, however, does not disrupt the differentiation and appearance of the principal retinal cell types at postnatal stages, even if the overgrowing retina covers finally the entire bulbus of the eye. Morpholino-mediated knock-down of the hist2h3ca1 gene in zebrafish leads to a specific perturbation of lens development. When injected into zebrafish zygotes, only the mutant mouse mRNA leads to severe malformations, ranging from cyclopia to severe microphthalmia. The wild-type Hist2h3c1 mRNA can rescue the morpholino-induced defects corroborating its specific function in lens development. Based upon these data, it is concluded that the ocular function of the Hist2h3c1 gene (encoding a canonical H3.2 variant) is conserved throughout evolution. Moreover, the data highlight also the importance of Hist2h3c1 in the coordinated formation of lens and retina during eye development. Highlights: A dominant small-eye mutant mouse is caused by a mutation in the histone gene Hist2H3c1. Morpholino-mediated knock-down of hist2h3ca1 in the zebrafish validated this finding. The mutation leads to degeneration of the lens vesicle and retina hyperproliferation.